2000
DOI: 10.2527/2000.7861667x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of protein concentration and degradability on performance, ruminal fermentation, and nitrogen metabolism in rapidly growing heifers fed high-concentrate diets from 100 to 230 kg body weight.

Abstract: Twenty crossbred heifers (101 +/- 4.5 kg BW) were used to examine the effects of protein concentration and degradability on performance, ruminal fermentation, nutrient digestion, N balance, and urinary excretion of purine derivatives. Heifers were offered concentrate and barley straw for ad libitum consumption. Two protein concentrations (17 vs 14%, DM basis) and two protein sources differing in ruminal degradability (58 vs 42% of CP for soybean meal and treated soybean meal, respectively) were tested. The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
44
2
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 28 publications
20
44
2
3
Order By: Relevance
“…However, in both treatments, heifers ate less forage than expected and much less than the level of 20% proposed by Forbes and Provenza (2000) for ruminants given a free choice between forage and concentrate. This result is in agreement with data obtained by Devant et al (2000) in young heifers (80 kg BW) given free-choice barley straw and concentrate in which they found a concentrate to forage ratio of 95 to 5, between the ratio recorded in the present experiment (96 to 4 and 94 to 6 for CH and TMR treatment, respectively). To design a TMR diet for young animals, it may be necessary to reduce the proportion of barley straw to fit the animals' requirements better.…”
Section: Figuresupporting
confidence: 93%
See 1 more Smart Citation
“…However, in both treatments, heifers ate less forage than expected and much less than the level of 20% proposed by Forbes and Provenza (2000) for ruminants given a free choice between forage and concentrate. This result is in agreement with data obtained by Devant et al (2000) in young heifers (80 kg BW) given free-choice barley straw and concentrate in which they found a concentrate to forage ratio of 95 to 5, between the ratio recorded in the present experiment (96 to 4 and 94 to 6 for CH and TMR treatment, respectively). To design a TMR diet for young animals, it may be necessary to reduce the proportion of barley straw to fit the animals' requirements better.…”
Section: Figuresupporting
confidence: 93%
“…However, young cattle fed diets based on concentrate and barley straw, offered both ad libitum and separately, consume the roughage in a much lower proportion. Devant et al (2000) reported that the concentrate : barley straw ratio decreased from 95 : 5 to 92 : 8 -E-mail: Alfred.Ferret@uab.cat in Friesian crossbred heifers from 80 to 230 kg BW. Gonzá lez et al (2008), working with Friesian heifers from 140 to 380 kg BW in feedlot conditions, reported an average concentrate : straw ratio of 89 : 11 when both ingredients were also offered separately and on an ad libitum basis.…”
Section: Introductionmentioning
confidence: 99%
“…There were not differences in acetate, propionate or butyrate proportions among treatments within each trial, and acetate:propionate ratios were representative of those reported in beef cattle fed high-concentrate diets (Devant et al, 2000;Martin et al, 2010), with an average value of 1.57. However, VFA concentration significantly varied along the time following a cubic relationship ( Figure 5.5.…”
Section: Influence Of Experimental Diets On Ruminal Fermentation Varisupporting
confidence: 51%
“…Cereal straw is fed ad libitum in order to maintain the rumen function and to reduce the impact of the high availability of starch (Gimeno et al, 2014), as straw promotes chewing and salivation and contributes to maintain the buffering capacity of the rumen. However, straw intake is generally low (below 12% of total DMI; Devant et al, 2000;Gimeno et al, 2014;Iraira et al, 2015), and related to the necessary quantity to maintain rumen functionality.…”
Section: The Role Of Forages In High-grain Concentrate Dietsmentioning
confidence: 99%
See 1 more Smart Citation